Denis Pankratov's Full Stroke at 65 m of His 100 m Butterfly Gold Medal Race at the Atlanta Olympic Games 1996 - Rushall, B. S. (1999)
Video pictures (17 frames) and the appropriate technical/ biomechanical explanations for Denis Pankratov's Full Stroke at 65 m of His 100 m Butterfly Gold Medal Race at the Atlanta Olympic Games 1996.